Design and Implementation of an IoT-Based Irrigation Management System for Alternate Wetting and Drying (AWD) Technique in Rice Cultivation - I Nyoman Teguh Yudha Kusuma; I Putu Gede Budisanjaya; Sumiyati Sumiyati; Andri Prima Nugroho; Ni Nyoman Sulastri; I Wayan Tika (The University of Lampung, 2025)
Rice irrigation management is facing considerable challenges, particularly in improving water use efficiency. This study aimed to develop an irrigation management system integrating the Alternate Wetting and Drying (AWD) technique with Internet of Things (IoT) technology. The system was constructed using ESP32 microcontroller, TOF10120 distance sensor for water level monitoring, an SD card module for data logging, 20×4 I2C LCD for real-time display, an optocoupler relay module for system control, and DS3231 real-time clock for timekeeping. Remote monitoring and control were enabled via the Blynk platform. System design was conducted using AutoCAD software, circuit simulations were performed using the Wokwi platform, and field testing was implemented in a rice cultivation area in Tabanan, Bali. Water level measurements were obtained using the TOF10120 sensor, and measurement accuracy was evaluated using MAPE (Mean Absolute Percentage Error). The system operated using a 100 WP solar panel and battery, ensuring sustainable and autonomous functionality. Results demonstrated that the IoT-based AWD irrigation management system successfully automated irrigation scheduling according to crop water requirements, achieving a high accuracy with a MAPE of 3.83%. Integration with the Blynk platform provided real-time monitoring and remote control functionalities, offering farmers an effective and user-friendly tool for optimizing irrigation water management. Keywords: Alternate Wetting and Drying (AWD), Automatic Irrigation System, Blynk platform, IoT, Irrigation management, Sensor.